2005
DOI: 10.1002/hep.20579
|View full text |Cite
|
Sign up to set email alerts
|

The human liver clears both asymmetric and symmetric dimethylarginine

Abstract: Asymmetric (ADMA) and symmetric dimethylarginine (SDMA) inhibit production of nitric oxide. The concentration of both dimethylarginines is regulated by urinary excretion, although ADMA, but not SDMA, is also subject to degradation by dimethylarginine dimethylaminohydrolase, which is highly expressed in the liver but also present in the kidney. The exact roles of the human liver and kidney in the metabolism of dimethylarginines are currently unknown. Therefore, we aimed to investigate renal and hepatic handling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
80
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 36 publications
10
80
0
1
Order By: Relevance
“…Liver lysates displayed four-to eightfold higher levels of free cellular ADMA and SDMA compared with the lung and heart. Because liver proteins did not exhibit a higher degree of protein-incorporated methylarginine, the increased ADMA and SDMA levels may be a result of active hepatic methylarginine uptake by the y ϩ transporter, as suggested in previously published studies (31,32). Liver lysates also exhibited significantly higher DDAH1 expression and ADMA degradation activity than did lysates from lung and heart tissue.…”
Section: Discussionmentioning
confidence: 50%
“…Liver lysates displayed four-to eightfold higher levels of free cellular ADMA and SDMA compared with the lung and heart. Because liver proteins did not exhibit a higher degree of protein-incorporated methylarginine, the increased ADMA and SDMA levels may be a result of active hepatic methylarginine uptake by the y ϩ transporter, as suggested in previously published studies (31,32). Liver lysates also exhibited significantly higher DDAH1 expression and ADMA degradation activity than did lysates from lung and heart tissue.…”
Section: Discussionmentioning
confidence: 50%
“…This calculation corrects a possible overestimation of the fractional renal extraction [calculated as (A Ϫ V)/A ϫ 100% (37,43,53)] in cases of a low renal plasma flow (3). A positive RPCL indicates net clearance of the substance from the blood, whereas a negative RPCL indicates net release into the blood.…”
Section: Methodsmentioning
confidence: 88%
“…This indicates that the plasma clearance of SDMA is not exclusively assigned to the kidney and implies that the plasma concentration of SDMA is not solely regulated by plasma clearance, as the plasma concentration is the result of the balance between production and clearance. Siroen et al (43) showed that the human liver also takes up substantial amounts of SDMA (and ADMA) from the portal and systemic circulation, which shows that the liver also contributes to the plasma clearance of SDMA. However, the results of a study (27) in subjects with hepatorenal syndrome suggested that renal dysfunction is the main determinant of increased SDMA concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent evidence does support a role for hepatic clearance of ADMA by DDAH. 21,22 Thus, with increased cholestatic liver damage there appears to be diminished capacity for hepatic ADMA metabolism contributing to increased circulatory levels, thereby perpetuating increased hepatic vascular tone.…”
mentioning
confidence: 99%